Epidemiology of Orofacial Clefts: A Spatio-Temporal Descriptive Analysis in Tripoli, Libya, 2017-2021 - Elfaidy, Yusra; Naas, Eman; Arebi, Arij; Alfowers, Hend; Albourawi, Hadil; Elyounsi, Surur; Aljhemi, Nooralhuda (AlQalam Journal of Medical and Applied Sciences, 2024)
Orofacial clefts are the most common congenital anomalies affecting the orofacial region. An abnormal facial development causes this congenital deformity during gestation; its aetiology is multifactorial. It is crucial to understand the prevalence of craniofacial anomalies in each community to determine the size of the problem, enhance the life standards for the patients, and assess the efficacy of interventions. In this study, we aimed to provide a picture of the prevalence of orofacial clefts in Tripoli, Libya. Also, it provides a useful reference for cleft-type distribution with their etiological risk factors. The data was collected from the archives of cleft babies referred to major specialized hospitals in Tripoli, Libya, from 2017 to 2021. Variables were collected and analyzed, including data related to cleft cases and their parents. During the study period, the incidence of orofacial clefts was 1.06 per 1,000 live births. The prevalence of cleft lip was 38.3%, cleft palate was 42.2%, and cleft lip with palate was 19.6%. The results showed that 2017 had the highest incidence rate, reaching 32.2%, while it was 8.3% in 2021. The prevalence was generally higher among males than females, at a difference rate of 3.47%. A history of folic acid deficiency and unsupervised drug intake during pregnancy was noted (58.3% and 61.7%, respectively). In addition, the higher prevalence was more common among mothers older than 34. Moreover, it has observed that 46.8% of patients` fathers were smokers. The study concluded that the incidence of cleft defects in Tripoli, Libya, was relatively low, and the role of the predisposing factors in increasing the incidence of cleft deformity remains uncertain. Further studies are recommended to find out the root cause. تعد الشقوق الفموية الوجهية من أكثر التشوهات الخلقية شيوعًا التي تصيب منطقة الوجه والفم. يحدث هذا التشوه الخلقي بسبب نمو غير طبيعي للوجه أثناء الحمل، وأسبابه متعددة العوامل. و من الأهمية فهم مدى انتشار الشذوذ القحفي الوجهي في كل مجتمع لتحديد حجم المشكلة، وتحسين معايير الحياة للمرضى، وتقييم فعالية التدخلات العلاجية. في هذه الدراسة، هدفنا إلى تقديم صورة عن مدى انتشار الشفة الأرنبية مع أو بدون الحنك المشقوق في طرابلس، ليبيا. وهدفنا أيضًا لتوفير مرجع مفيد لتوزيع أنواع تشوهات الشقوق الفموية الوجهية وعوامل الخطر المسببة لها. تم جمع بيانات هذا البحث من ملفات الأرشيف للأطفال المصابين الذين تم إحالتهم إلى المستشفيات المتخصصة الرئيسية في طرابلس، ليبيا، للفترة من 2017 إلى 2021م. تم جمع المتغيرات، بما في ذلك البيانات المتعلقة بتلك الحالات وآبائهم، وتحليلها. خلال فترة الدراسة، بلغ معدل حدوث الشفة الأرنبية مع أو بدون الحنك المشقوق 1.06 لكل 1000 ولادة حية. ومن إجمالي عدد الحالات، كان معدل انتشار الشفة الأرنبية 38.3%، والحنك المشقوق 42.2%، والشفة الأرنبية مع الحنك المشقوق 19.6%. وأظهرت النتائج أن عام 2017 كان أعلى معدل انتشار، حيث بلغ 32.2%، بينما كان 8.3% في عام 2021. وبالإضافة إلى ذلك كان معدل الانتشار أعلى عمومًا بين الذكور منه عن الإناث، بمعدل فرق 3.47%. كما سجلت حالات عدم تناول حمض الفوليك اللازم بنسبة 58.3%، وحالات تناول لأدوية بدون إشراف طبي أثناء فترة الحمل بنسبة 61.7%. ولوحظ أن معدل الانتشار الأعلى كان أكثر شيوعًا بين الأمهات فوق سن 34 عامًا. علاوة على ذلك، وجد أن 46.8% من آباء الأطفال المصابين هم من المدخنين. وخلصت الدراسة إلى أن معدل حدوث تشوهات الشقوق الفموية الوجهية في طرابلس، ليبيا، كان منخفضًا نسبيًا، ولا يمكن التأكيد على دور العوامل المذكورة في زيادة الإصابة بهذه التشوهات، كما لا يمكن استبعادها. ويوصى بإجراء المزيد من الدراسات لمعرفة العوامل الرئيسية المسببة